Formulasi Gel Handsanitizer Minyak Atsiri Daun Sereh (Cymbopogon nardus) dengan Hidroxy Propyl Methyl Cellulose (HPMC) sebagai Gelling Agent - Febriza Risti Widyastuthi; Yohanes Juliantoni; Eustachius Hagni Wardoyo (Fakultas Farmasi Universitas Pancasila, 2020)
Gel handsanitizer wich is sell in the market today is mostly alcohol-based. Repeated useas a handsanitizer can cause dryness and irritation skin. An option is, we can substitute an alcoholinto lemongrass oil (Cymbopogon nardus). There are three steps of the test, a preliminary test of oilconcentration, a test of the physical properties of the gel preparation and a modifi ed replication test.Based on the preliminary test, citronella essential oil can kill Escherichia coli bacteria at a concentrationof 5% and reduce Staphylococus aureus at 10% of concentration. The test of spread for gel in thephysical test is between 5.5-6 cm with pH 7-9 and the adhesion is 1 second.The modifi ed replica testshowed a signifi cant decrease in the number of bacterial colonies at each concentration formula ofthe three test groups. This signifi cance indicates the inhibition of bacteria caused by the use of handsanitizing gels. Based on the organoleptic test and antibacterial test of hand sanitizer gel a chosenconcentration is 10%. This concenrtration was liked by the public and could inhibit bacterial growth.